Economic and bioenergetics efficiency of the use of bio drugs when cultivating peas - G. M. Sitalo; L. P. Beltyukov (Зерновое хозяйство России, 2018)
Economic and bioenergetics efficiency of the use of bio drugs when cultivating peas The field trials were conducted in the southern zone of the Rostov region in 2014-2016 with the non-leafy morphotype of the pea variety ‘Angela’ to identify the best drugs used for its cultivation. In the experiments we used such preparations as ‘Rizotorfin’, ‘Ekstrasol’, ‘Vigor Forte’, ‘Mival Agro’ and ‘Flavobacterin’. They were twice used in the treatment of seeds before sowing and in the period of plant cultivation during the phase of 3-5 leaves. The trials showed that all studied bio preparations had a positive effect on pea yield increase. In this case, the double application of ‘Mival Agro’ (20 g/t) in the treatment of seeds before sowing and in the period of plant cultivation (20 g/ha) turned to be the most effective. In this case the maximum yield of seeds was 3.47 t/ha, the highest net income was 17908 rubles/ha, the lowest production cost was 4839 rubles/t with the rate of profitability of 107%. In the same version of the experiment, the largest obtained energy income was 40739 MJ/ha and the coefficient of energy efficiency (CEE) was 3.0.